Pemberdayaan Petani: Penguatan Kapasitas Petani dalam Meminimalisir Modal dan Pengembangan Hasil Tani di Desa Atiran - Baihakki, Fajar; Hakim, Arif Rahman; Safitri, Erlinda Septia; Salasiah; Saputra, M Rizky Yuanda; Bahran; Damayanti, Rismi; Amalia, Nur; Riswanda, Noor Akhmad; Afifah, Siti; Zhafira, Ananda Salma (Hayak Bamara: Jurnal Pengabdian Masyarakat, 2024)
Atiran Village is a village located in the Meratus Mountains, Batang Alai Timur District, Hulu Sungai Tengah Regency. This village makes farmers the main livelihood and has a fundamental problem in the form of not developing the capacity of farmers and still doing farming in a normative way. This makes Atiran village farmers will never get maximum profit and farmers experience economic stagnation, which is a condition where there is no economic development that only meets substantial needs. These problems are the main background of the service carried out by the service team to increase the capacity of farmers with the IPO model (input, process, output) to get more accurate results in analysis and activities. The purpose of this program is to overcome the problems of farmers who have not been able to do farming that is more in accordance with the conditions of the village location and make farmers more independent to overcome problems. The implementation method uses intervention logic designed based on the thoughts of David Easton and Wassily Leontief regarding the input, process, and output models. The service activities were carried out live in or settled at the service location for 57 days which lasted from 18 July 2024 to 12 September 2024, so that the service team could be intensely involved with community activities and build closer interactions. The results achieved by this program are farmers who have new skills in the form of making organic fertilizers and herbicides, then there is cooperation with the Agriculture Office regarding the ongoing program so that farmers have clarity about the management of the resulting farm products. With this program, the service team is confident and believes that farmers will get a change in economic income.